Influence of Physical Work Environment and Stress on Employee Performance: The Crucial Role of Job Satisfaction - Mustika, Yunanda Alya; Azzuhri, Misbahuddin (Jurnal Kewirausahaan dan Inovasi, 2025)
Understanding the factors that influence employee performance is critical for organizational success. This study examines the impact of the physical workplace environment and job stress on TVRI Central Java employees’ performance, with job satisfaction as a mediating variable. A quantitative explanatory approach was used, involving all 162 employees, with data collected through Likert-scale questionnaires and analyzed using SPSS version 29. The analysis included path analysis and hypothesis testing.The findings show that: (1) the physical workplace environment has a positive and significant effect on job satisfaction; (2) job stress positively influences job satisfaction; (3) the physical workplace environment does not directly affect employee performance; (4) job stress does not directly impact employee performance; (5) job satisfaction positively affects employee performance; (6) the physical workplace environment indirectly affects performance through job satisfaction; (7) job stress also indirectly affects performance through job satisfaction.This research provides new insights into the role of workplace factors and stress in shaping employee performance, highlighting the importance of managing the physical environment and stress to improve organizational outcomes.